Unlocking the keto code : the revolutionary new science of keto that offers more benefits without deprivation - Gundry, Steven R. (Harper Wave, an imprint of HarperCollinsPublishers, 2022)
"The author of the Plant Paradox series introduces the new science of keto and shows how you can eat a much wider variety of foods to get more benefits with less side effects"--